Implementasi Kepemimpinan Kepala Sekolah SMPN 61 Surabaya dalam Transformasi Menjadi Sekolah Wisata Edupark dan Inovasi Kepemimpinan - Indri Ribbut Aprilla; Marselina Nango; Ima Widiyanah; Karwanto Karwanto (Jurnal Penelitian, 2025)
Educational transformation in the modern era requires adaptive, innovative, and visionary school leadership. SMPN 61 Surabaya introduces a new paradigm through its initiative to transform into an Edupark Tourism School, integrating the concept of edutourism into the formal educational environment. This article aims to examine the implementation of school leadership in this transformation process, focusing on the innovative strategies applied, the challenges faced, and their impact on school culture and student learning. This study employs a descriptive qualitative approach using in-depth interviews, participatory observation, and documentation. The research sample consists of 1 principal (Mr. Darto), 7 teachers across subjects, and 5 students actively involved in the Educational Tourism Park School activities. The results of the study indicate that the implementation of school leadership in this transformation is effective, with the main characteristics of transformational leadership, namely providing inspiration (85%), intellectual stimulation (80%), individual attention (75%), and ideal influence (90%). The principal's managerial skills were highly rated by teachers (82%) in terms of programme planning, activity organisation, and management of partnerships with external parties. Meanwhile, the use of leadership power, such as referent power (88%) and expert power (84%), was proven to increase the active participation of teachers and students. In the context of leadership politics, the principal successfully built consensus and united the various interests of the school community with an effectiveness rate of 79%. Overall, the principal's leadership demonstrated a strategic role in transforming the school into a creative, collaborative, and contextual learning space. This transformation not only strengthened the character of the students but also opened up space for more meaningful learning innovations. These findings are expected to serve as practical and theoretical references for other educational institutions seeking to implement a similar model.